Increasing Corporate Value through ESG: The Role of Financial Performance as a Mediating Variable - Fanniya Dyah Prameswari; Mona Tiorina Manurung (P3M Politeknik Negeri Banjarmasin, 2026)
This research investigates how ESG implementation impacts Firm Value and explores whether financial performance acts as a mediating variable. Additionally, it assesses the influence of board meeting frequency and board size on Firm Value. The study uses a quantitative methodology, analyzing panel data from companies listed on the ESG IDX during the 2023–2024 period through regression analysis techniques. The findings show that companies demonstrating stronger ESG practices and corporate governance quality typically receive higher investor confidence and more favorable market ratings, leading to an increase in Firm Value. However, neither board meeting frequency nor board size was found to have a statistically significant effect on Firm Value in this model. The mediation analysis also reveals that financial performance does not mediate the relationship between ESG implementation, board meeting frequency, or board size and Firm Value. Thus, these factors appear to influence Firm Value more directly rather than indirectly through changes in financial performance within the observed sample.